Mengenal Mindfulness Bagi Siswa SMA - Sandra Sutanto; Grace Immanuela (Devotion : Jurnal Pengabdian Psikologi, 2022)
Teenagers live among the hustle bustle world, which makes them constantly have to think about anticipating problems and career in the future, to find solutions and solving problems in the past. These two conditions, added with the problem of their task to settle their identity often make adolescents stress, have relationship problems, experience certain psychological symptoms or disorders, and do not fully live in the moment. Mindfulness method is believed as a method that helps teen to live in the present. They can be fully focuses on what they are doing the moment, increase responsiveness and awareness while experiencing emotional distress This mindfulness method will be given in the webinar for Athalia High School students, consist of information and practical tips of mindfulness. The webinar will consist of two sessions, a conceptual introduction session on the theory and uses of mindfulness for adolescents and a mindfulness training session, with each session lasting 45 minutes. The question and answer session will conclude the webinar, followed by a survey of evaluation on the webinar.